KEDUDUKAN ANAK MENURUT HUKUM POSITIF DI INDONESIA - MAGHFIRAH, SA'DATUL (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2016)
Undang-undang Nomor 23 Tahun 2002 which is revised by Undang-undang Nomor 35 Tahun 2014 about child protection chapter 1 verse 1 points out that child are those who are under 18 years old, including the fetus. Those laws regulate the position of children in the law and their rights as well, and parents’ responsibilities toward their children. Chapter 42-49 of UndangUndang Nomor 1 Tahun 1974 points out that child’s positions can be classified into two categories, namely legal and illegal child depending upon the ways their parents get married. If their parents’ married has fulfilled marital requirements both in terms of religion and law implemented in Indonesia the child resulted from this marriage is categorized into legal child. Conversely, if a child was born from parents whose marriage does not fulfill the requirements, the child, therefore, belongs to illegal child categories. Civil law in Indonesia has regulated rights a child deserves as stated in Undang-Undang Republik Indonesia Nomor 4 tahun 1979 concerning with Child Prosperity found in Chapter II and Undang-undang Nomor 23 Tahun 2002 jo Undang Undang Nomor 35 Tahun 2014 that covers rights to live, to be non discriminative, to have identity, to be treated fairly, and so forth in line with parents’ responsibilities toward children so that they are treated properly and live prosperously